Role of men in promoting the uptake of HPV vaccinations: Focus groups' finding from a developing country - Wong, L.P. (Birkhauser Verlag Ag, 2010)
Better outcomes of human papillomavirus (HPV) vaccination would be expected if men become full partners and advocates in vaccination initiative. Men involvement has important implication especially within the context that they are equally responsible for spreading the virus. Twenty-seven men took part in four focus group discussions carried out to assess men's attitudes toward the HPV vaccine between October and November 2007. The results revealed that men have low awareness about the newly release vaccine and minimal knowledge of HPV and its association with cervical cancer. When provided with information, most men were in favor of protecting their spouses, partners, or daughters from cervical cancer using the vaccine. They were aware of the effects of men's risk behavioral patterns on women's risk for acquiring HPV infections. Many needed assurance about the vaccine's long-term safety and efficacy. They also expressed concern over the high cost of the vaccine. Men in this study played an influential role in the vaccination decision of their child and sexual partners. Many were in favor of male vaccination for cervical cancer prevention of their spouse or partner. Vaccine advocacy should put special emphasis on men as sexual partners, husbands, and fathers from a gender equality and partnership perspective. The findings are useful in facilitating the development of strategies for effective immunization initiatives.